Comparative Study of Indonesian Seismic Codes Applied on Vertically Irregular RC Building in High Seismicity Region - Ibnu Syamsi, Muhammad; Maulana, Taufiq Ilham; Widyantama, Hararya; Ian, Muhammad Rezki; Lesmana, Redi Indra (International Journal of Integrated Engineering, 2021)
The Aceh earthquake suffering Indonesia in 2004, and some big ground motions afterward led the earthquake-resistant building standard provisions to be updated. The rise of ground motions increases the lateral forces, so reevaluating existing buildings is needed, especially for Irregular buildings, which are more vulnerable than the regular ones. This study investigates the increase of earthquake loads and the building response in the high seismicity region due to the updated Indonesian code from SNI 1726:2002 to SNI 1726:2012. Building A in DI Yogyakarta with vertical irregularity on a certain floor is chosen as the object to be studied. There are two types of seismic loads to be simulated, response spectrum and time history analysis. The building is simulated using the numerical program, and four ground motion histories are selected for the dynamic exiting forces. The analysis result shows an increase in the story force either in the response spectrum or the time history. By taking the building's top floor as the reference point, the increase in lateral displacement is also detected in both response spectrum and time history analysis. From the interstory drift ratio examinations, it is also found that there is a weak point located on the setback part that is not identified just by observing the total displacement. This paper compiles the comparison of two versions of the Indonesian seismic code, two types of seismic force, and two points of view in analyzing the building response. Furthermore, the result presented in this paper also beneficial for mitigating the building.